Comparison of broth microdilution, broth disk elution and automated system results in determining vancomycin susceptibilities of Staphylococcus aureus strains - Tuğba Ayvalık; Emel Sesli Çetin (Journal of Global Antimicrobial Resistance)
Background: The broth disk elution (BDE) method has been recommended by CLSI as an alternative to the broth microdilution (BMD) method, which is the reference method for determining the colistin susceptibility of Gram-negative bacteria, since it is more affordable and unlaborious. The aim of this study was to compare the results of BMD, BDE and automated system in determining the vancomycin susceptibility of Staphylococcus aureus strains. METHODS: A total of 60 S. aureus strains, 30 methicillin-susceptible S. aureus (MSSA) and 30 methicillin-resistant S. aureus (MRSA) strains, were included. BMD was applied according to CLSI and EUCAST recommendations, and the BDE method was adapted from the colistin BDE method of CLSI guidelines (Table 1). Tests were performed in duplicate for each strain. RESULTS: BMD and BDE results of all strains showed 100% categorical agreement. The minimum inhibitory concentrations (MICs) of 3 strains determined by BDE were higher than those determined by BMD. The automated system and BMD results showed 95% categorical agreement. The major and very major error rates of the automated system was found to be 5% and 0% respectively (Table 2). Conclusions: The BDE method can be safely applied in laboratories that cannot perform BMD to determine the vancomycin MICs of S. aureus strains, but strains interpreted as resistant by BDE should be confirmed by BMD. It should also be kept in mind that automated system vancomycin MIC results for S. aureus strains may have high error rates.